Fair Wind: Medicine and Consolation on the Berens River - Brown, Jennifer; Matthews, Maureen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1993)
AbstractFair Wind (Naamiwan) was an Ojibwa healer and leader widely known along the Berens River of Manitoba and northwestern Ontario in the early to mid-twentieth century. In the 1930s he became acquainted with the American anthropologist, A.Irving Hallowell, whose writings and photographs first drew our attention to Fair Wind's life and to the significance of his distinctive drum ceremonial, the roots of which extended to the Drum Dance that originated in Minnesota in the 1870s. This paper traces his life and explores the nature of his religious leadership, drawing upon the recollections of his descendants as well as on the records left by Hallowell and the numerous fur traders, missionaries, and others who visited the region during his long lifetime ( 1851-1944).